Binding mechanism and distant regulation of histone deacetylase 8 by PCI-34051 - Yuxiang Luo; Zhaoyue Yan; Xiakun Chu; Ying Zhang; Yufan Qiu; Huilin Li (Communications Biology)
Abstract Histone deacetylase 8 (HDAC8) is a well-known epigenetic regulator for cancer therapy. However, developing targeted inhibitors for HDAC8 is challenging due to a limited understanding of its structural dynamics, which is crucial for ligand interaction. Here, we employed an integrated approach, including native mass spectrometry (native MS), hydrogen-deuterium exchange mass spectrometry (HDX-MS), and molecular dynamics (MD) simulation, to investigate the inhibition mechanism and dynamic regulation of human HDAC8 (hHDAC8) by selective inhibitor PCI-34051, compared with the pan-inhibitor SAHA. Our results revealed that PCI-34051 engages with an expanded set of residues and conforms more aptly to the binding channel of hHDAC8, stabilizing the flexible loops surrounding the binding channel. Moreover, this dynamic stabilization effect is not limited to the binding regions, but also extends to distant regions (such as L2, α5, and α1 + α2), with L3 serving as a critical structural bridge. Overall, these results show the structural and dynamic regulations of hHDAC8 by PCI-34051, which induces a lower energy state for the protein-ligand system compared to SAHA, thus showing better inhibitory effects. In addition, it also suggests that certain regions, specifically loops L2 and L3, within the hHDAC8 protein could be key regions for targeted intervention.